Elevated homocysteine, glutathione and cysteinylglycine concentrations in patients homozygous for the Chuvash polycythemia VHL mutation - Sergueeva, Adelina I. (2008)
In Chuvash polycythemia, homozygous von Hippel-Lindau (VHL) 598C>T leads to increased hypoxia inducible factor-1α and 2α, thromboses and lower systemic blood pressures. Circulating homocysteine, glutathione, γ-glutamyltransferase and cysteinylglycine concentrations were higher in 34 VHL598C>T homozygotes than in 37 normal controls and cysteine was lower. Multivariate analysis showed elevated homocysteine independently associated with higher mean systemic blood pressures and elevated glutathione was associated with lower pressures to a similar degree. Among VHL598C>T homozygotes, homocysteine was elevated with low and normal folate concentrations, consistent with a possible defect in the remethylation pathway. The elevated glutathione and γ-glutamyltranserase levels correlated positively with cysteinylglycine, consistent with possible upregulation of a glutathione synthetic enzyme and γ-glutamyltransferase. Cysteinylglycine correlated inversely with cysteine, consistent with possible reduced cysteinyldipeptidase activity. We conclude that up-regulated hypoxia-sensing may influence multiple steps in thiol metabolism. The effects of the resultant elevated levels of homocysteine and glutathione on systemic blood pressure may largely balance each other out.